Repair of Bone Defects with Chitosan-Collagen Biomembrane and Scaffold Containing Calcium Aluminate Cement - Moraes,Paola Castro de (2017)
Abstract Innovative biomaterials can provide a promising new direction for the treatment of bone defects, stimulating a proper repair process, with no damage to adjacent tissues. The purpose of this in vivo study was to evaluate the biocompatibility and the osteoinductive capacity of chitosan-collagen biomembrane and scaffold containing calcium aluminate cement. Eighteen New Zealand white rabbits (Oryctolagus cuniculus) were distributed according to the experimental times of analysis (7, 15 and 30 days). Four bone defects were created in the rabbits calvaria, which were individually filled with the biomembrane, scaffold, blood clot (negative control) and autologous bone (positive control). Histopathological analysis was performed using optical microscope at 32´, 64´, 125´ and 320´ magnifications. Cell response to inflammation and new bone tissue formation was quantified using a score system. The biomembrane group presented greater inflammatory response at 15 days, with significant difference to autologous bone group (p<0.05). There was no statistically significant difference for foreign body type reaction among groups (p>0.05). Concerning new bone formation, linear closure of the defect area was observed more evidently in the group with autologous bone. The scaffold group presented similar results compared with the autologous bone group at 30 days (p>0.05). Both tested biomaterials presented similar biocompatibility compared with the control groups. In addition, the biomembrane and scaffold presented similar osteoinductive capacity, stimulating bone repair process in the course of the experimental time intervals.